HEAVY METALS CONCENTRATIONS AND THEIR HEALTH RISK ASSESSMENT IN SOIL FROM BOKO HARAM’S AFFECTED AREAS OF GOMBE STATE, NIGERIA - BABA, A. M.; MAITERA, O. N.; MAINA, H. M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The research was aimed to evaluate the concentration of some heavy metals and their health risk assessment in the soil samples from Boko Haram attacked areas of Gombe State. The samples were collected from the affected sites (Gombe division, Quarter guard, Kwadon police Station, D/Kowa Park, K/mata, Timber Market and Gombe Main market in Gombe Metropolis, Nafada Police Station and Nafada Mosques in Nafada, Bajoga Police Station, Ashaka Junction, GRA, and Union Bank in Bajoga Town) and the metals concentrations were determined using Energy Dispersive X-Ray Fluorescence (EDXRF) Spectrometry. The results indicated that the mean concentrations of the metals in the study area ranged as follows; Cr=19.6-58.3Mg/kg; Ni=2.76- 12.6Mg/kg; Cu=17.5-60.1Mg/kg; Zn=6.08-1,460Mg/kg; As=1.75-30.20Mg/kg; and Pb=3.57- 196Mg/kg. All the metals investigated in all the samples were found to be below their Maximum Permissible Limits, (MPL) set by WHO except Zn (300Mg/kg) in Gombe Division, D/Kowa Park and Timber Market, Pb (100Mg/kg) in D/Kowa Park and As (20Mg/kg) in Quarter guard. Risk characterization which predicts the potential non-carcinogenic and carcinogenic health risk on populace in the study area was carried out by integrating all the information gathered to arrive at quantitative estimates of hazard and cancer risk indices. The Hazard index, HI which represent the potential non-carcinogenic risk posed by more than one metal ranged from 0.0171-0.9621. This indicates that all the samples had HI values <1 and hence, the exposed population is unlikely to experience adverse health effects. The incremental probability of an individual developing cancer over a lifetime as a result of exposure to the potential carcinogen, called the Risk Index, RI indicates that all the sites had RI values >1.0E-4 except K. police Station, K/Mata, BJ Police station, Ashaka Junction and GRA sites. This shows pollution that may pose cancer risk to the adult populace. Therefore, most Boko Haram attacked sites in the study area were found to be polluted by heavy metals as shown by the risk indices values and comparison of the metal’s concentration in the affected sites and that of the control samples where there were no attacks.